The R369 Myosin Residue within Loop 4 Is Critical for Actin Binding and Muscle Function in Drosophila. - Trujillo, A.S.; Hsu, K.H.; Viswanathan, M.C.; Cammarato, A.; Bernstein, S.I. (International journal of molecular sciences, 2022)
The myosin molecular motor interacts with actin filaments in an ATP-dependent manner to yield muscle contraction. Myosin heavy chain residue R369 is located within loop 4 at the actin-tropomyosin interface of myosin's upper 50 kDa subdomain. To probe the importance of R369, we introduced a histidine mutation of that residue into Drosophila myosin and implemented an integrative approach to determine effects at the biochemical, cellular, and whole organism levels. Substituting the similarly charged but bulkier histidine residue reduces maximal actin binding in vitro without affecting myosin ATPase activity. R369H mutants exhibit impaired flight ability that is dominant in heterozygotes and progressive with age in homozygotes. Indirect flight muscle ultrastructure is normal in mutant homozygotes, suggesting that assembly defects or structural deterioration of myofibrils are not causative of reduced flight. Jump ability is also reduced in homozygotes. In contrast to these skeletal muscle defects, R369H mutants show normal heart ultrastructure and function, suggesting that this residue is differentially sensitive to perturbation in different myosin isoforms or muscle types. Overall, our findings indicate that R369 is an actin binding residue that is critical for myosin function in skeletal muscles, and suggest that more severe perturbations at this residue may cause human myopathies through a similar mechanism.